CLASSROOM ACTION RESEARCH: IMPROVING SPEAKING SKILL BY USING SIMULATION STRATEGY FOR HOTEL ACCOMMODATION STUDENTS (ESP) AT SMK NEGERI 3 PALANGKA RAYA - Parianson, Taguh; Bungai, Joni; Bahing, Bahing (Program Studi Magister Pendidikan Bahasa Inggris, Program Pascasarjana, Universitas Palangka Raya, 2023)
This research has been designed as collaborative classroom action research to improve the speaking skill of teaching English for specific purpose by using simulation strategy for Hotel Accommodation students at SMK Negeri 3 Palangka Raya. The previous generations of the school mostly got poor score at the final proficiency competency test due to the lack of specific English teaching for hotel. The research focused on how the teaching English for specific purpose – “Front Office subject” – by using simulation strategy can improve the speaking skill of Hotel Accommodation students at SMK Negeri 3 Palangka Raya – especially on escorting the hotel guest? This research was designed as collaborative classroom action research (CCAR); collaborated with the colleague – teacher – who teaches “Front Office” at the same class. The action research steps implemented for this research was adapted from Ferrance and Seberova and Maleik. The simulation strategy and the specific purpose approach in teaching English have improved the students’ speaking skill. There were so many advantages in implementing this strategy specifically to the vocational school students. The students were highly motivated in learning English. They may use their English speaking skill sustainably for their future. They felt free to practice speaking English contextually, and may learnt in peer collaboratively during the teaching learning time. The impact was shown on their speaking score - focused on fluency, pronunciation, utterance, and supportive body language - which has reached satisfying mean score. They also may enlarge their utterance skillfully due to the realia taken to the real English class. The simulation strategy – combined with role-play and drilling by delivering ESP material, performed with Genre-Based approach was highly recommended to be applied more and more in English speaking class at vocational school.